STAEM VALVES AND STEAM TRAPS FOR THERMAL POWER STATION - JANKAR, Mr. SUNIL; RATHORE, Prof. R S; GUPTA, ASHOK KUMAR (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
There are different types of valve available for industrial application as per the requirement. valves are classified based on material use, based on application, based on function etc. No steam system is complete without that crucial component 'the steam trap' (or trap). This is the most important link in the condensate loop because it connects steam usage with condensate return. A steam trap quite literally 'purges' condensate, (as well as air and other incondensable gases), out of the system, allowing steam to reach its destination in as dry a state/condition as possible to perform its task efficiently and economically.